Galeri Seni Rupa dengan Pendekatan Arsitektur Neo Vernakular Di Kota Medan - Wiro Krisman Halawa; Rahmadhani Fitri; Novalinda (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Art galleries are a place for art lovers who are used as a medium of interaction between artists and art connoisseurs. In the city of Medan there are communities of art lovers that are possible to develop. However, these communities cannot develop because of the activities carried out separately. The Medan art gallery will be a solution to the problem of the limitations of art lovers in the city of Medan. The purpose of this study is to examine the Medan Fine Art Gallery with an approach to the elements of Neo-Vernacular Architecture and develop it in a more modern form. In the design of the Medan Fine Arts Gallery, there are three main functions, namely without the visual arts communities in the city of Medan, Wadah trades the works of Medan children, and develops a creative economy which includes applying elements of the Neo-vernacular Architecture theme. This theme can be a basic reference in design as well as a unique value that displays the overall design result. The theme approach will produce a modern form but still have local cultural values. The concept is "Batak Traditional House and Ulos Fabric motif" which is one of Medan's cultural icons. Overall the building characterizes predetermined themes and concepts. A combination of themes and concepts that will produce a modern form but still apply local cultural values.